Stigma-Based Bullying Interventions: A Systematic Review - Earnshaw, Valerie A. (Dev Rev, 2018)
Youth living with socially devalued characteristics (e.g., minority sexual orientation, race, and/or ethnicity; disability; obesity) experience frequent bullying. This stigma-based bullying undermines youths’ wellbeing and academic achievement, with lifelong consequences. The National Academies of Sciences, Engineering, and Medicine recommends developing, implementing, and evaluating evidence-based interventions to address stigma-based bullying. To characterize the existing landscape of these interventions, we conducted a systematic review of stigma-based bullying interventions targeting youth in any country published in the peer-reviewed literature between 2000 and 2015. Our analysis was guided by a theoretical framework of stigma-based bullying, which describes stigma-related factors at the societal, structural, interpersonal, and individual levels that lead to stigma-based bullying. We screened 8,240 articles and identified 22 research studies describing 21 interventions addressing stigma-based bullying. We found that stigma-based bullying interventions are becoming more numerous, yet are unevenly distributed across stigmas, geographic locations, and types of organizations. We further found that these interventions vary in the extent to which they incorporate theory and have been evaluated with a wide range of research designs and types of data. We recommend that future work address stigma-based bullying within multicomponent interventions, adopt interdisciplinary and theory-based approaches, and include rigorous and systematic evaluations. Intervening specifically on stigma-related factors is essential to end stigma-based bullying and improve the wellbeing of youth living with socially devalued characteristics.